Service Quality Impact on Customer Satisfaction of Multipurpose Loan Products - Jaenudin Jaenudin; Evi Verawati (BASKARA : Journal of Business and Entrepreneurship, 2022)
This study aims to determine: How the influence of service quality on customer satisfaction at PT WOM Finance Kemayoran Branch, Central Jakarta. This research is a quantitative study. The research location is PT WOM Finance, Kemayoran Branch, Central Jakarta. The population in this study were customers of PT WOM Finance Kemayoran Branch, Central Jakarta, the sampling method was carried out by the random method, and using the Slovin 79.36 formula rounded up to 80 respondents. Based on the results of partial hypothesis testing, the T-test of the Service Quality variable obtained a T-count value of 7,297 while the statistical table (T table) was 1,665 and the significance value of the Service Quality variable was 0.000 less than 0.05. So it can be concluded that Service Quality partially has a positive and significant effect on Customer SatisfactionKeywords: Service Quality, Customer Satisfaction